Anxiety as a prevailing factor of performance of university mathematics students during the COVID-19 pandemic - D. Mendoza; M. Cejas; G. Rivas; C. Varguillas (Образование и наука)
Introduction. Anxiety is characterised by feelings of tension, apprehension or fear. It arises from concern about student performance at university, with an emphasis on exact science subjects. It is not only students, who suffer from mathematical anxiety. However, anxiety is a predominant factor in student performance at all levels.The aim of the research was to describe the levels of anxiety also known as distress manifested by university mathematics students studying at the Universidad Nacional de Chimborazo (UNACH) during the 2020-1 academic semester.Methodology and research methods. The current study was carried out applying the quantitative paradigm. It is of a descriptive exploratory design. The total sample consisted of 120 students, who are preparing at their university level, and, who are studying the subject of mathematics at different levels and careers at UNACH. The selection of the sample was of an intentional non-probabilistic type and having as inclusion criteria not having been diagnosed with an anxiety disorder. As a measurement instrument, the Short Inventory of Anxiety Situations and Responses-ISRA-B was applied. ISRA-B was sent to students by email to facilitate data collection.Results. The results were analysed by means of the two-factor ANOVA calculation (mathematics and understanding). The results showed that there are statistically significant differences in the understanding of the contents presented by the teachers in a virtual way. During the COVID-19 pandemic the levels of mathematical anxiety increased. Teaching mathematics at university in online format requires the assessment of digital connection and time limited submission of assignments. These factors limit understanding and generate mathematical anxiety. Scientific novelty. In face-to-face education, mathematical anxiety is common. But because of the pandemic, mathematics education has had to migrate to the virtual environment. The present research reflects the impact of anxiety not only on mathematics education and academic performance but also on the emotions of students. The data collection instruments ISRA-B-C, ISRA-B-F and ISRA-B-M are innovative and adaptable to all levels of education.Practical significance. The importance of mathematics and the overestimation of its difficulties cause great concern for the learning of this subject in studies at a higher university level. The current studies of virtual mathematical anxiety are important because they allow the detection and analysis of possible educational failures in online learning. The failures of online education have a direct impact not only on performance and learning, but on an emotional state of students.